The timing of exogenous ethylene supplementation differentially affects stored sweetpotato roots - Amoah, Robert Sarpong; Landahl, Sandra; Terry, Leon A. (Elsevier, 2016)
The effects of continuous supplemental ethylene (10 μL L−1) timing on the physiology and biochemistry of sweetpotato roots during storage at 25 °C were examined. Alongside continuous ethylene or air treatments, a subset of the roots were transferred at dormancy break, from those previously stored in ethylene into air and vice-versa. The study showed distinctive ethylene-induced effects on the metabolism of individual sugars, phenolic compounds and phytohormones (abscisic acid and zeatin riboside) across the spatial gradient of the root flesh and skin tissues. Although ethylene flushing doubled root respiration, sprout growth was significantly suppressed. Supplementation of roots with ethylene after dormancy break effectively inhibited sprout growth as much as continuous ethylene alone. On the other hand, truncating ethylene application after dormancy release promoted vigorous sprout growth. After prolonged storage, ethylene treatment was associated with increased weight loss and incidence of proximal rots. Supplemental ethylene also accelerated the catabolism of monosaccharides, and promoted accumulation of phenolic compounds in the proximal root sections.
Keywords: Respiration; Sprouting; Sugars; Phenolics; Abscisic acid